Penerapan Program Pemberdayaan Keluarga Sebagai Upaya Meningkatkan Status Fungsional Klien dan Kesiapan Keluarga Merawat Klien Stroke - Arista, Liya; Nurachmah, Elly; Herawati, Tuti (UIMA Press, 2020)
Introduction: Stroke is a condition of brain function loss due to disturbance in cerebral blood flow that occurs more than 24 hours. The difficulties and dysfunction are caused by brain damage entail long-term disorders of physical and mental balance, so that the patients depend on their families. Objective: The aim of this study was to assess the impact of the family empowerment program on the functional status of patients after stroke and also family preparedness to taking care the patients at home. Method: The study design was a quasi-experiment design with pretest-posttest control group approach using 25 respondents. Groups were divided into a control group (n=12) and intervention group (n=13). Results: The results showed that is no significant difference between functional status in both groups after the intervention, but there is a significant difference in family preparedness to taking care for stroke survivors between the control and intervention groups (p = 0.004 at α = 0.05). Conculsion: Based on the results, the provision of family empowerment program as a preparation for discharge planning could be one of the nursing interventions for families to giving a care for stroke survivors at home